Critical Review of the Meaning of the Concept of Love - Wahyu Trisno Aji; Luis Santos; Nguyen Minh Tu (International Journal of Educatio Elementaria and Psychologia, 2024)
The purpose of this research is to explain how the concept of love is interpreted, love is a mystery that is always hot to discuss, and even love has existed since the first humans, namely Adam and Eve. This type of research uses descriptive qualitative, using a library research approach with documentation data collection techniques. The research results obtained are: 1) Understanding love is not only about having feelings or fighting for them, but also about having emotional readiness to face negative consequences, such as heartbreak. Practicing self-defense in love, such as through self-dichotomy and an antifanatic attitude towards falling in love, can help a person face love more calmly and wisely. 2) True love certainly exists, at least he understands self-maturation and is aware of the importance of understanding love. When they grow and develop into people full of art. That's when they understand love as eros, agape and selfssness. Love can be studied, understood, worked for and fought for even though it is without reason and full of sacrifice.